If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-4=-3+4x
We move all terms to the left:
3x-4-(-3+4x)=0
We add all the numbers together, and all the variables
3x-(4x-3)-4=0
We get rid of parentheses
3x-4x+3-4=0
We add all the numbers together, and all the variables
-1x-1=0
We move all terms containing x to the left, all other terms to the right
-x=1
x=1/-1
x=-1
| 5u-13=3u+8+2u | | (10-2x)^3=70 | | 4(6x-3)=60 | | 2F-11=3f+18 | | y=4/5.3+√0.75+0.2-5.75 | | 5x+3=-7+6-13x | | -1/2x-2=-8 | | 16x÷2=4.8 | | 1200-2x=6x | | 2500=x-0.1x-200 | | 2x=4/3x^2 | | 11.22=4.9x^2 | | 5x-15=3-x | | x+30+2x=10-4x | | 7x+2=5x-12 | | 3xx2x=100 | | 5/4+y=-10 | | 4x-x^=0 | | 7(5b+6)=-6 | | 5^2-20x=0 | | 1/8+x=3/4 | | 3x-14=8x+13 | | 5y-2=3y+18 | | 12+z=20 | | 24÷n=4 | | 5x/7+2/7-3x/2+1/2=5/14 | | 3x-11=-15 | | (3x-1)(x-4)=16 | | 2^2x-3(2^x)+2=0 | | 6p+8=4p+18 | | 4(x-5=48 | | x/5=2,1/2 |